Urban transformations as a sustainable urban development strategy: experiences, typological proposal, prospective for Colombia (REVISTA NODO, 2021)
This article exposes the nature of urban transformations as a model of urban planning and management-oriented towards the recovery and renovation of places and spaces in urban and peripheral areas. The objective is to identify the benefits in the environmental, social and economic dimensions of cities, and that are generated with the implementation of urban transformations. The methodology is oriented to the study of successful experiences in the global, Latin American and Colombian context; through the characterization of the antecedents and problems in each case, the planning and management processes, and the results of the implementation around the environmental, physical, social and economic system that make up a city. The results are a typological proposal of categories of urban transformations according to their nature and the city-systems on which they have the greatest effects; also a discussion on its implementation in Colombia. It concludes on the need for a broad typological classification applicable in various contexts, and the implementation scenario of urban transformations in Colombian cities.
Keywords: Urban area; Public works; Quality of life; Urban planning; Sustainable development